Medicinal Plants for Traditional Treatment Used by the Malays in South Bangka Regency, Indonesia - Henri Henri; Dayu Puspita Sari; Luchman Hakim (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
The people of South Bangka Regency have been well-known for using plants as traditional medicine and applied it in their daily life, but the information about the indigenous medical system the limited written of documentation. This study aimed to describe the types of medicinal herbs, analyze the medicinal herbs used as traditional medicine, and discover the conservational effort practiced by the Malays which is the local ethnic of South Bangka Regency. The study employed a quantitative method with field observation techniques, interviews, and herbs identification. The data were analyzed using the ethnomedicinal quantitative method. The results showed that there were 117 species of medicinal herbs with 57 families, while the most frequently used herb was Areca catechu with the results of UV (0.16), FL (16.22), and RFC (0.004). On the important family value (FIV), the most frequently used herb was the Myrtaceae family with 9 species, followed by Poaceae with 8 species. One of the conservation efforts of medicinal plants is by conducting cultivation to help prevent extinction in their natural habitat.